Pengaruh Project Based Learning terhadap Kemampuan Berpikir Kritis Siswa Kelas V SD Islam Istiqomah - Tata Listiyawati; Atrianing Yessi Wijayanti; Nimas Puspitasari (Lembaga Pengembangan Kinerja Dosen, 2025)
Education is a crucial foundation for shaping a generation with strong character, faith, intelligence, and responsibility as mandated by Law Number 20 of 2003. In the 21st century, one of the most essential competencies to be developed is critical thinking, which can be effectively nurtured through Project Based Learning (PjBL). This approach actively engages students in planning, inquiry, problem-solving, and reflection within project-based tasks, making learning more meaningful. This study examines the effect of PjBL on the critical thinking skills of fifth-grade students in Natural and Social Sciences (IPAS) at SD Islam Istiqomah, Ungaran Barat, Semarang Regency. Employing a quantitative method with a quasi-experimental Nonequivalent Control Group Design, the study involved 76 students divided into experimental and control groups. Data were collected using a validated and reliable essay test on critical thinking skills. Results showed that the experimental group achieved a higher mean posttest score (84.16) than the control group (74.74). The point-biserial correlation was rpb = 0.676, and the t-test result (tcount 7.891 > ttable 1.993, p < 0.05) confirmed a significant difference. These findings demonstrate that PjBL substantially improves students’ critical thinking and emphasize its continued implementation to foster contextual and meaningful IPAS learning.